Geospatial Validation for Task Letter Automation in Tomohon City: Validasi Geospasial untuk Otomatisasi Surat Tugas di Kota Tomohon - Moningkey, Efraim; Atuna, Annisa Salsabilah; Santa, Kristofel (Universitas Muhammadiyah Sidoarjo, 2025)
General background. Digital transformation is central to modernizing public services and improving administrative reliability. Specific background. At the Tomohon City Land Office, manual task letter issuance and attendance monitoring often cause delays and errors. Knowledge gap. Previous research largely focused on GPS-based attendance systems without integrating automated task letter generation. Aims. This study aims to develop a web-based information system integrating task letter automation and geospatial attendance validation using the Haversine algorithm. Results. The system automatically generates task letters, embeds geolocation data, and verifies officer attendance within a specified radius in real time. Testing confirmed accurate distance calculations, reduced administrative errors, and improved task monitoring. Novelty. The integration of Haversine-based geospatial validation with administrative automation in the land sector represents a unique contribution to digital governance. Implications. The system provides a scalable model for modernizing bureaucratic processes and supports Indonesia’s e-government initiatives through accurate, real-time monitoring of field activities. Highlight Development of a web-based system integrating task letter automation and geospatial validation Accurate attendance verification through the Haversine algorithm in real time Supports bureaucratic modernization and e-government initiatives in the land sector KeywordWeb Based Information System, Haversine Algorithm, Task Assignment, Attendance Monitoring, E-Government